Behavior of a Discrete Fractional Order SIR Epidemic Model - George Maria Selvam, A.; Abraham Vianny, D. (International Journal of Engineering and Technology, 2018)
In this paper we investigate the dynamical behavior of a SIR epidemic model of fractional order. Disease Free Equilibrium point, Endemic Equilibrium point and basic reproductive number are obtained. Time series plots, phase portraits and bifurcation diagrams are presented for suitable parameter values. Also some numerical examples are provided to illustrate the dynamics of the system.Â Â